Experimental vaccination against Newcastle disease in Japanese quails (Coturnix coturnix japonica): Clinical and immunological parameters - Paulillo, Antonio Carlos [UNESP] (2009)
Clinical and immunological parameters of vaccinated Japanese quails against Newcastle disease were evaluated. Two-hundred and forty birds were distributed into five different experimental groups, vaccinated or not against Newcastle Disease (ND): G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain), G4 (LaSota strain inactivated and emulsified in mineral oil) and G5 (not vaccinated-control). The immune response was evaluated by the HI test. The vaccinations of Japanese quails with NDV LaSota strain inactivated and emulsified in mineral oil strain produced high antibody levels. Ulster 2C, B1 and LaSota live strains produced moderated antibody levels and did not cause any clinical signs associated with post-vaccinal reactions. © Asian Network for Scientific Information, 2009.